Transparent coating materials based on inorganic/organic composites - Srikulkit, Kawee; Rojtinnakorn, Naparath; Charoensak, Rajcharoj (Journal of Metals, Materials and Minerals, 2017)
A siloxyl group functionalized copolymer of low molecular weight was synthesized, aiming at preparing transparent inorganic/organic coating composites. Two types of coating systems were investigated: two-component system (based on functionalized copolymer-HMMM) a three-component system (based on functionalized copolymer-HMMM-TEOS). Their properties were investigated and compared. Coating films obtained from these systems exhibited good optical clarity, which was largely dependent on the content of indicated Materials. For instance, to prevent phase separation in the 3component system, TEOS was â€œeffectivelyâ€ linked to pendent siloxyl groups on the organic moiety Hence, coating formulations containing a high degree of pendent siloxyl groups exhibited better optical transparency. These coating systems improved abrasion/scratch resistance properties of coated/cured PC sheets Further investigation for the system properties revealed that two crosslinked networks were responsible for the coating film hardness : an organic network resulting from transetherification between copolymer hydroxyl group and HMMM methylol group, and an inorganic network resulting from a sol-gel reaction The inorganic network was the main contributer to the improved surface performance of coated PC samples.